Panen Pucuk dan Buah pada Tanaman Leunca (Solanum nigrum L.) yang Dipupuk dengan Dosis Nitrogen Berbeda - Nani Yulianti; Edi Santosa; Anas Dinurrohman Susila (Institut Pertanian Bogor, 2020)
The increasing popularity of leaf and fruit of African nightshade as vegetables in Indonesia stimulates farmers to harvest both leaf and fruit from single plant alternately; the yield is presumably affected by fertilizer rate, e.g., nitrogen. The present study aimed to evaluate such hypothesis through evaluation of plant production, N absorption, and its status. Seedlings were treated with five N levels, i.e., 0, 90, 180, 270, and 360 kg/ha in Leuwikopo Experimental Farm, IPB Bogor, Indonesia. The results revealed that leaf and fruit productions were sensitive to nitrogen level. Leaf and fruit productions had quadratic correlation to N levels, i.e., r 2=0.9671 and r 2=0.9483 with optimum dosages as 304.8 kg/ha and 336.5 kg/ha, respectively. Proper N application is important for both leaf and fruit productions because nitrate level in leaf had quadratic relationship (r 2=0.5264) and it has a linear relationship in fruit production (r2=0.9587) by increasing N level from 90 to 360 kg N/ha. From the total fresh mass leaves and fruits harvested, the optimum N for the best alternate harvesting was 271.1 kg/ha (r 2=0.9644). Keywords: African nightshade, intercropping, N uptake, nitrate status, photosynthetic rate